(3fXQjGJ GdEYdGe h GJLGgGJ GdJCKjQ (B/s - (3YHO GdMejO, eMeOs ((3GdbGgQI (B:s (3YGde GdcJH ,s, 2004)
(3JJLOO WHYGJ gPG GdcJGH JdHjI dMGLI GdecJHI GdYQHjI Gdi OQGSI MQcI GdYedjI GdEYdGejI h YfGUQgG aj YdGbJgG Hcd Gdbhi GdeDKQI aj GdeLJeY h HUa NGUI LeghQ hSGFd GdEYdGe aj EWGQ GdeaGgje h GdfXQjGJ GdeJLOOI GdJj bOeJ QUOG YdejG dgPg GdYdGbGJ h JCKjQGJgG GdeJHGOdIs
(3HjHd(B.:(3U(B.469-485s
Keywords: (3GdGJUGds; (3GdGJUGd GdQbejs; (3fXQjGJ GdEYdGes; (3GdEYdGes